Baseline susceptibility of an A1 quarantine pest - the South American tomato pinworm Tuta absoluta (Lepidoptera: Gelechiidae) to insecticides: past incidents and future probabilities in line to implementing successful pest management - Bavithra, Chandra Mohan Muthu Lakshmi; Murugan, Marimuthu; Balasubramani, Venkatasamy; Harish, Sankarasubramanian; Prakash, Kolanchi (Frontiers in Plant Science, 2024)
Tomato is a widely cultivated crop significant for its economic and nutritional benefits. The South American tomato pinworm, Tuta absoluta, originated in Peru South America and has invaded many nations, causing up to 100% yield loss in tomatoes. The pest was classified as a quarantine pest by the European Plant Protection Organization, before invading the Spain region. Later, this quarantine pest also invaded other regions of Europe, Africa and Asian countries. Invasive insect pests cause global economic losses of 70 billion dollars annually. Among the several management measures suggested against pests, insecticides are the primary method in practice among growers due to significant results, easier operations, and other crucial advantages. Anyhow, repeated application of insecticides has caused the pest to evolve resistance against most of the insecticides in vogue, resulting in a chain of events like management failures, using increased doses of insecticides, intensified chemical residues in the food chain, and irreparable environmental contamination. Major insecticides globally used to control T. absoluta belong to organophosphates, synthetic pyrethroids, neonicotinoids, diamides, avermectins, spinosyns, and oxadizines. Understanding the baseline susceptibility of pests to insecticides helps for better pest management options and is the same for T. absoluta populations to insecticides. The current review paper discusses the T. absoluta distribution, biology, spread, host range, baseline insecticide susceptibility, global insecticide resistance status, and possible management inputs based on our understanding of insecticide susceptibility. The pest can be managed with integrated insecticide resistance management including molecular approaches.